2018
DOI: 10.1016/j.concog.2017.10.011
|View full text |Cite
|
Sign up to set email alerts
|

Daydreams incorporate recent waking life concerns but do not show delayed (‘dream-lag’) incorporations

Abstract: This study investigates the time course of incorporation of waking life experiences into daydreams. Thirty-one participants kept a diary for 10 days, reporting major daily activities (MDAs), personally significant events (PSEs) and major concerns (MCs). They were then cued for daydream, Rapid Eye Movement (REM) and N2 dream reports in the sleep laboratory. There was a higher incorporation into daydreams of MCs from the previous two days (day-residue effect), but no day-residue effect for MDAs or PSEs, supporti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 52 publications
0
10
0
Order By: Relevance
“…Where the Friedman test was significant, a Wilcoxon signed-rank test was used to compare means of the three combined time periods that are used to test for the day-residue and dream-lag effects, namely the mean of 1 and 2 days, mean of 3 and 4 days, and mean of 5, 6 and 7 days. These periods were defined in advance and in accordance with the literature (Blagrove, Fouquet et al, 2011;Nielsen et al, 2004;van Rijn et al, 2015van Rijn et al, , 2018. Day-residue and dream-lag effects were predicted for the incorporation of PSEs; hence, the means of the number of PSE incorporations for the periods 1-2 days and 5-7 days F I G U R E 1 (a) Schematic of the experiment.…”
Section: Discussionmentioning
confidence: 99%
“…Where the Friedman test was significant, a Wilcoxon signed-rank test was used to compare means of the three combined time periods that are used to test for the day-residue and dream-lag effects, namely the mean of 1 and 2 days, mean of 3 and 4 days, and mean of 5, 6 and 7 days. These periods were defined in advance and in accordance with the literature (Blagrove, Fouquet et al, 2011;Nielsen et al, 2004;van Rijn et al, 2015van Rijn et al, , 2018. Day-residue and dream-lag effects were predicted for the incorporation of PSEs; hence, the means of the number of PSE incorporations for the periods 1-2 days and 5-7 days F I G U R E 1 (a) Schematic of the experiment.…”
Section: Discussionmentioning
confidence: 99%
“…Studies evaluating which elements of waking events appear in dreams have shown that many dreams can be traced back to events occurring during the day preceding the dream -a phenomenon referred to as day-residue effect (de Saint-Denys, 1867; Nielsen and Powell, 1992). Some studies have also provided evidence for a dream-lag effect, that is, another temporal peak of integration of elements from events occurring about a week before the dream (Nielsen and Powell, 1992;Van Rijn et al, 2015;van Rijn et al, 2018). It remains open whether it is specific to certain types of events (Vallat et al, 2017;Veloce et al, 2019) and sleep stages (Blagrove et al, 2011).…”
Section: Dreams Are Associated With Reduced Reflective Consciousnessmentioning
confidence: 99%
“…Although waking experiences are not faithfully replayed in dreams ( Fosse et al , 2003 ), dream content arises from waking-life experiences ( Stickgold et al , 2001 ; Nielsen and Stenstrom, 2005 ; Eichenlaub et al , 2017 ). The notion that dreaming is connected with experiences of the immediately preceding days was described by Freud using the term ‘day-residues’ ( Freud, 1953 /1900), and, more recently, numerous studies have refined this phenomenon ( Nielsen and Powell, 1989 ; Powell et al , 1995 ; Nielsen et al , 2004 ; Schredl, 2006 ; Blagrove et al , 2011 a, b ; van Rijn et al , 2015 , 2018 ; Vallat et al , 2017 a). In addition, the nature of the daily experiences incorporated into dreams has been explored, highlighting that emotional and personally significant experiences are preferentially incorporated ( Cartwright et al , 1998 b, 2006 ; Schredl, 2006 ; Propper et al , 2007 ; Malinowski and Horton, 2014 ).…”
Section: Introductionmentioning
confidence: 99%